Behind the scenes at the Science Museum - Macdonald, Sharon Jeannette 1961- (Routledge, Taylor & Francis, 2020)
What goes on behind closed doors at museums? How are decisions about exhibitions made and who, or what, really makes them? Why are certain objects and styles of display chosen whilst others are rejected, and what factors influence how museum exhibitions are produced and experienced? This book answers these searching questions by giving a privileged look behind the scenes at the Science Museum in London. By tracking the history of a particular exhibition, Macdonald takes the reader into the world of the museum curator and shows in vivid detail how exhibitions are created and how public culture is produced. She reveals why exhibitions do not always reflect their makers original intentions and why visitors take home particular interpretations. Beyond this local context, however, the book also provides broad and far-reaching insights into how national and global political shifts influence the creation of public knowledge through exhibitions
"First published 2002 by Berg Publishers.
Keywords: Science Museum (Great Britain); Science museums / Educational aspects / England / London; Science / England / London / Exhibitions; Sciences / Musées / Aspect éducatif / Angleterre / Londres; Sciences / Expositions / Angleterre / Londres; SOCIAL SCIENCE / Anthropology / General; Science; Science museums / Educational aspects; England / London / https://id.oclc.org/worldcat/entity/E39PBJp68ckpMtKGHPFWQrwDMP; Exhibition catalogs